A new infraspecific taxon of Phyllanthus myrsinites (Phyllanthaceae) from the Brazilian Amazon - Secco, Ricardo De S. (Phytotaxa, 2013)
Phyllanthus myrsinites subsp. platyphyllus, a new subspecies from Amazonas States, Brazil, is described and illustrated. It differs from Phyllanthus myrsinites subsp. myrsinites in its wide-orbiculate leaves that can be up to 2.7 cm wide, with a subapical gland 4–5 mm from the apex, secondary veins evident on the adaxial surface, and staminate flowers grouped only in the leaf axils.